The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1136/bmjdrc-2020-001413
|View full text |Cite
|
Sign up to set email alerts
|

Impact of type 2 diabetes and microvascular complications on mortality and cardiovascular outcomes in a multiethnic Asian population

Abstract: IntroductionDiabetes mellitus is a growing public health epidemic in Asia. We examined the impact of type 2 diabetes, glycemic control and microvascular complications on mortality and cardiovascular outcomes in a multiethnic population-based cohort of Asians without prior cardiovascular disease.Research design and methodsThis was a prospective population-based cohort study in Singapore comprising participants from the three major Asian ethnic groups: Chinese, Malays and Indians, with baseline examination in 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…( 16 ) In addition, the results of the severity analysis similarly confirmed that all grades of retinopathy were significant associated with DM-specific causes of death, and the trend test was also significant ( P for trend <0.05), the DM-specific HR increased exponentially with increasing retinopathy severity, and patients with PR had the highest risk of DM-specific death (HR = 13.62, 95% CI: 2.52–73.75). As for the reasons why grading of retinopathy was associated with the trend of increased DM-specific mortality risk, the results of a multi-ethnic Asian population study showed that survival rates of DM patients without microvascular disease were similar to those of non-DM patients after approximately 7 years, ( 48 ) suggesting that the lesion burden of the microvasculature in DM patients predicts an increased mortality risk. As previously described, the retina is the only site where blood vessels are directly visible, and the grading of retinopathy obtained by fundus photography may be an indicator of systemic microvascular disease characteristics, which could explain the fact that increased severity of retinopathy leads to an exponential increase in the DM-specific mortality risk.…”
Section: Discussionmentioning
confidence: 99%
“…( 16 ) In addition, the results of the severity analysis similarly confirmed that all grades of retinopathy were significant associated with DM-specific causes of death, and the trend test was also significant ( P for trend <0.05), the DM-specific HR increased exponentially with increasing retinopathy severity, and patients with PR had the highest risk of DM-specific death (HR = 13.62, 95% CI: 2.52–73.75). As for the reasons why grading of retinopathy was associated with the trend of increased DM-specific mortality risk, the results of a multi-ethnic Asian population study showed that survival rates of DM patients without microvascular disease were similar to those of non-DM patients after approximately 7 years, ( 48 ) suggesting that the lesion burden of the microvasculature in DM patients predicts an increased mortality risk. As previously described, the retina is the only site where blood vessels are directly visible, and the grading of retinopathy obtained by fundus photography may be an indicator of systemic microvascular disease characteristics, which could explain the fact that increased severity of retinopathy leads to an exponential increase in the DM-specific mortality risk.…”
Section: Discussionmentioning
confidence: 99%
“…The microcirculation is emerging as a major determinant of cardiovascular outcomes among patients with and without DM (19). This study aimed to ll this gap and evaluate the effectiveness of using ceramide as a biomarker for microvascular disease.…”
Section: Discussionmentioning
confidence: 99%
“…First, high NLR values promoted the development and acceleration of diabetic microvascular complications, including diabetic retinopathy, nephropathy, and peripheral neuropathy [ 46 , 47 ]. Patients with increasing burden of microvascular complications were at risk for higher mortality and poorer cardiovascular outcomes [ 48 ]. Second, hyperglycemia with increased NLR was related to increased complexity and severity of coronary lesions [ 49 ].…”
Section: Discussionmentioning
confidence: 99%